O ambiente da periferia: conflitos sociais e riscos nas políticas urbanas em Fortaleza-Ceará - Soares, Jacqueline Alves (2011)
The research seeks to understand the relationship between housing and the environment by analyzing the conflicts involving municipal urban project to eliminate risk areas. The challenge that arises is to observe whether such risk prevention policies and environmental disasters in urban areas have been changing the forms (or ways) of space production towards greater environmental justice. It starts from the assumption that the measures presented for hazardous areas of residents by not attacking the source of generating problems of environmental inequality, present ineffective and poor solutions keeping the imprisoned population to the circuit of risk, and present while legitimizing discourse of gentrification of the area. The residents, in turn, develop strategies of resistance through new allocations of meaning of "risks" as a discursive strategy of power. Such analysis is done empirically from case study involving the Municipal Program of Urban Requalification and Social Inclusion - PREURBIS in hazardous areas at a place called Boa Vista, located in the middle course of Rio Coco, Fortaleza-Ce. The area where the population is being allocated also presents risks due to the new dwelling location being situated in the surroundings of the landfill ‘Jangurussu’. From the material point of view these "struggles for ratings" articulate and redefine material disputes between the defense of living of this low-income population in an area well located and well served by public facilities and urban interventions that have valued the space in the capitalist logic, inducing the replacement of the former inhabitants by other higher-income inhabitants and retention of urban land for speculative purposes. We adopted a qualitative methodology with literature review, document research, participant observation and interviews.